Preferensi Pakan dan Kebutuhan Nutrien Anoa Gunung (Bubalus quarlesi Ouwens 1910) pada Kondisi Prabudidaya - M Basri; . Suryahadi; T Toharmat; H S Alikodra (Media Peternakan, 2008)
The aim of this study was to obtain information in relation to kind of forest plants which were usually consumed by mountain anoa in its natural habitat and community area around the forest, and to estimate energy and nutrient requirements for maintenance and growth of anoa. This study was conducted in Province of Central Sulawesi using six anoas. Digestal analysis method was used to study kind of forest plants in the rumen of anoas. Cafetaria system was used to obtain information related to the dry matter intake of forest plants. Regression analysis was used to estimate energy and nutrient requirements of anoa. The results showed that anoa consumed Ficus vasculosa Rump (fruits), Scleria purpurescens (leaves), Ficus sp. (shoots), Brachiaria mutica (leaves) and Ipomea aquatica Fordk (leaves and stems). The dry matter intake of these feeds were 29.1 ± 8.5, 16.5 ± 3.8, 14.2 ± 2.8, 7.6 ± 1.7 and 4.8 ± 0.6 g/kg W0.75, respectively. The energy and nutrient requirements of anoa for maintenance based on g/kg W0.75 were 22 g TDN, 6.3 g protein, 0.457 g Ca and 0.427 g P. The energy and nutrient requirements of anoas for growth based on g/kg weight gain were 1333.64 g TDN, 399.9 g protein, 29.38 g Ca and 26.85 g P. Key words: anoa, feed preference, nutrient requirements